ORGANOLEPTIC QUALITIES, METABOLITE PRODUCTS AND DIGESTIBILIY OF DRY AND ORGANIC MATTER OF ELEPHANT GRASS SILAGE (Pennisetum purpureum) WITH VARIOUS LEVELS OF BREAD WASTE - I M. K. A., Bhuana; Mudita, I M.; Cakra, I G. L. O. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the organoleptic quality, metabolite products and digestibility of dry matter and organic matter elephant grass silage ( Pennisetum purpureum ) with various levels of bread waste. This study was conducted at the Sesetan Research Station and Laboratory of Nutrition and Animal Feed, Faculty of Animal Science, Udayana University, which was conducted from July-September 2020. The design used was a completely randomized design (CRD) consisting of 4 treatments, namely elephant grass silage ( Pennisetum purpureum ) + 0% bread waste (P0), silage 90% elephant grass ( Pennisetum purpureum ) + 10% bread waste (P1), silage 80% elephant grass ( Pennisetum purpureum ) + 20% bread waste (P2), silage 70% elephant grass ( Pennisetum purpureum ) + 30% bread waste (P3). Each treatment had 4 replications. The variables observed were organoleptic qualities ??including color, odor, texture, mold and pH value, VFA and NH 3 production, and dry matter and organic matter digestibility. Collcect data were analyzed by analysis of variance. The results showed quantitatively P3 produced the best color, odor and texture, while P2 and P3 had no mold, P3 treatment got the lowest pH value (P<0,05) of 4.236, the highest VFA production (P>0,05) was 75,77 mM, and the highest dry matter and organic matter digestibility (P<0,05), respectively 69.019% and 67.352%. P2 treatment obtained the highest NH 3 production (P>0,05) of 3.681 mM. From the results of the study it can be concluded that bread waste can improve the quality of silage through organoleptic assessment, dry matter digestibility and organic matter as well as VFA and NH 3 production. Keyword : elephant grass silage, bread waste, organoleptic, digesibility, metabolite products